[PP.34.38]: INCIDENT ATRIAL FIBRILLATION IN LONG-TERM FOLLOW-UP OF CRYPTOGENIC STROKE. (June 2015) - Alonzo>, C.>; Brescacin, L.; Zurru, M.; Linares, G.; Pigretti, S.; Camera, L.; Cristiano, E.; Waisman, G.
Abstract : Objective: Even after an extensive evaluation, the cause of an ischemic stroke remains unexplained in 20 to 40% of patients, resulting in the classification, by exclusion, as cryptogenic stroke. Atrial fibrillation (AF), a well-recognized risk factor for ischemic stroke, is often difficult to diagnose given its paroxysmal or asymptomatic nature. We aim to identify risk factors for developing AF after a cryptogenic stroke. Design and method: Acute ischemic stroke patients were prospectively included in PROTEGE-ACV, a multidisciplinary secondary stroke prevention program. Demographic data and pre-stroke vascular risk factor profile and control were obtained from electronic medical records, acute and previous vascular lesions were identified on admission- MRI and inflammatory markers were measured one month after stroke. Incident AF was assessed after two years of follow-up. Physiopathological mechanisms of stroke were identified according to TOAST classification. A univariate analysis and a logistic regression model were performed. Results: After a comprehensive evaluation, 541 (44%) of 1215 stroke patients included between December 2006 and December 2013 were classified as TOAST 5 (undetermined). After two years of follow-up, 246 of them (40%) had incident AF. These patients were older (78 ± 7 vs 72 ± 10, p 0.00001), female (62% vs 50%, p 0.001), had severe stroke (NIHSS > 10: 57% vs 31%, p 0.001), more prevalence of hypertension (92% vs 78%, p 0.0001) and chronic kidney disease (38% vs 22%, p 0.0001). They also had higher levels of hs-CRP (7 ± 10 vs 3 ± 6, p 0.001), lower e-GFR (60 ± 21 vs 70 ± 28 ml/min/1.73 m2, p 0.0004) and multiple acute and chronic ischemic lesions on MRI (22% vs 5%, p 0.001). Predictors for incident AF are shown in the table. Figure. No caption available. Conclusions: Beside well-known risk factors for AF (age and female sex) and clinical characteristics linked to cardioembolic stroke (multiple brain lesions and severe stroke), we identified inflammatory status and impaired renal function, both related with endothelial dysfunction and microvascular damage, as strong predictors of incident AF in long-term follow-up. These findings could help to increase clinical awareness on symptoms related to cardiac arrhythmias in stroke patients.